The metaphoric conception of national character in Abay Kunanbayev’s works - Orynkhanova, Gibadat; Nurlanova, Assem N.; K.Sabyrbaeva, Raushan; Amankulova, Laila A.; Tolegenov, Talgat (Opción, 2020)
The study aims to investigate the metaphoric conception of national character in Abay Kunanbayev’s works via comparative qualitative research methods. As a result, the essence of metaphor is a transposition of identifying (descriptive and semantically diffusive) vocabulary, intended to indicate the subject of the speech, in the sphere of predicates, intended to indicate its characteristics and properties. In conclusion, all deep thoughts of Abay were connected with this ideal dictated by the works of Sufi thinkers, Al-Farabi, IbnArabi, Al-Gazali.